A influência das brincadeiras no desenvolvimento da criança surda na educação infantil - (:unkn) unknown (Universidade Brasil, 2022)
This article aims to analyze the contributions of games and games in the development of teaching and learning of deaf children in Early Childhood Education. The methodology adopted was that of bibliographical research with theoretical foundation based on the authors: Huizinga, Vygotsky and Piaget. The justification is anchored in the relevance of the theme in the current scenario of inclusion for the construction of a more just and egalitarian society. It is concluded, therefore, that playing contributes significantly to the teaching-learning process of both hearing and deaf children.
Keywords: Brincadeiras; Criança surda; Educação infantil; LLA